Fated for felony - Laurie, Victoria (Laurie, Victoria. Psychic eye mystery series, 2019)
"In New York Times bestselling author Victoria Laurie's newest Psychic Eye Mystery, Abby is after a serial killer who's simply fated for felonies. When three newbie agents at the Austin's FBI cold-case bureau resent having to work alongside a psychic consultant, Abby Cooper finds herself in hot water after they contact super-popular podcaster Mike Toscano--a former agent and huge skeptic of Abby's abilities. To prove that she's the real deal, Abby will have to solve Toscano's oldest--and coldest--case, and she'll have to do it on air with millions of Toscano's fans critiquing her every move. To make matters worse, the D.C. brass is threatening to shut down the Austin offices if Abby doesn't bring home a win. But helping to solve the unsolvable is what Abby does best, and she'll be bringing her A-game to Toscano's podcast. The only trouble is the killer could be listening..."--provided by Amazon.com.